Analysis of The Effect of Company Size Leverage Company Value and Corporate Sustainability Index on Profitability (Case Study of a Sustainable Company Best 2022) - Warani, Sabrina Hindun Azah (Economics and Business International Conference Proceeding, 2024)
This study aims to determine influence Size Company, Value Company, Price to Book Value, and Corporate Sustainability Index to Profitability in Sustainable Companies Best 2022. The objects analyzed are 30 Mining Companies, 10 Plantation Companies, and 18 Food and Beverage Companies that have high CSI value in 2022 which can be found at https://databoks.katadata.co.id/. A total of 58 samples were obtained from 3 companies. The company namely Food and Beverage Companies, Mining Companies, and Plantation Companies. The analysis model used in this research is ROA = f (SIZE, DER, PBV, CSI). Research result show that X1 has no effect to variable Y, while variables X2, X3, X4 influential on variable Y. For research furthermore recommended to explore other possible factors influential to profitability. Factors​ this could be innovation, quality, management, strategy marketing, or condition economy.